Acute and chronic toxicity of a polyherbal preparation - Jueyin granules - Yu Chen; Dong-jie Guo; Hui Deng; Min-feng Wu; Ya-Nan Zhang; Su Li; Rong Xu; Jie Chen; Xing-xiu Jin; Bin Li; Qi Xu; Fu-lun Li (BMC, 2018)
Abstract Background The potential toxicity of Chinese herbal medicine has attracted more attention in recent years. Jueyin granules (JYG), a polyherbal formula, have been proven to be an effective agent for treating psoriasis in both animal models and clinical research. However, little is known about the possible acute and chronic toxicity of JYG. The objective of this study was to investigate the safety of JYG in ICR mice and Wistar rats. Methods To examine the acute toxicity of JYG, ICR mice were randomly divided into an experimental group and a control group, each comprising 20 mice (10 male and 10 female). The experimental group was fed JYG solution at a dose of 21.5 g/kg, equivalent to 143 times the clinical human dosage, for 14 days, whereas control animals were fed distilled water. In the chronic toxicity test, Wistar rats were divided into four groups, each comprising 40 rats (20 male and 20 female). For 6 months, the experimental animals were given JYG at a dose of 7.5, 3.75 and 1.875 g/kg, whereas control animals were given distilled water. The animals' body weight, food and water consumptions were monitored weekly. In addition, their biochemical and hematological parameters, histopathology, and body and organ weights were all measured at specific observation time points. Results According to the results of the acute toxicity test, no mortality was found and no abnormal pathological changes in major organs were observed in mice treated with JYG. In the chronic toxicity test, JYG did not cause significant abnormalities in the physiological parameters or pathological changes in the major organs of the rats. Conclusion The results indicated that JYG at the given doses did not induce any harmful effects in animals. Thus, it is reasonable to conclude that JYG is safe at the studied dosage levels and causes no acute or chronic toxicity in animal models.